Pengaruh Motivasi Kerja Dan Inovasi Produk Terhadap Keberhasilanusaha Batik Di Jambi Kota Seberang - Aleksander Sianturi, Ados; Muazza, Muazza; Sri Dwijayanti, Novia (Jurusan Pendidikan IPS FKIP UNJA, 2023)
This study aims to determine the effect between variables, namely regarding work motivation and product innovation on the success of the batik business in Jambi City of Seberang. This research is a quantitative research. The population in this study were batik business students in Jambi, Seberang City, with 44 batik entrepreneurs as respondents. The data collection technique was carried out by distributing questionnaires (hard files) directly to the respondents. The data analysis technique used is multiple linear regression analysis with the help of the SPPS 25.0 for windows program. The results of this study indicate that there is a positive influence of work motivation on business success seen in the value of tcount > ttable, namely 4.034 > 2.019. And there is a positive influence of product innovation on business success seen in the value of tcount > ttable, namely 4.044 > 2.019. Based on the results of the F test, the value of Fcount > Ftable is 10.586 > 3.23, so Ha is accepted, Ho is rejected, so there is a significant influence between work motivation and product innovation on business success